Caracterización del aislamiento social e impacto emocional por COVID-19. Gobierno Autónomo Descentralizado, Riobamba, 2021. - Chávez Peñafiel, Valeria Alejandra (2022)
The project has carried out in the Decentralized Autonomous Government of Riobamba (GADR). The objective was to analyze the social isolation and emotional impact by covid-19 of the GADR, 2021. The research has a quantitative approach, cross-sectional design, non-experimental and descriptive level; the population consisted of 1200 public servants in the administrative area and obtained a probability sample of 204 individuals. Used a sociodemographic card for getting the data; it used the Jong Gierveld loneliness scale to identify social isolation and the depression, anxiety, and stress scale (DASS 21) for emotional impact. The results indicated that: 41.2% of the study population presented moderate, severe, and maximum social isolation; as for the emotional impact, mild to highly intense levels have evidenced, of which 34.8% showed anxiety, 21.6% stress, and 22.1% depression; it has determined that the average degree of loneliness prevailed concerning the moderate to extremely severe levels of anxiety, stress, and depression. In conclusion, the population studied shows behaviors such as withdrawal, physical and mental fatigue, irritability, and mood swings; likewise, the emotional impact has evidenced in three emotional states: anxiety, stress, and depression, of which pressure predominates.